1970
DOI: 10.3329/agric.v9i1-2.9473
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Jam from Sapota (<i>Achras zapota</i>)

Abstract: An attempt was made to develop sapota jam to assess its prospect in marketability. The fruits were collected from local market and the pulp was extracted in the laboratory. Then the pulp was analyzed monthly for proximate composition. The proximate analysis of sapota pulp showed moisture 70.07%, ascorbic acid 8.90 mg/100g, pH 5.10, TSS 19.4% and total sugar 16.07%. No special change of ingredients was found during two months of storage. But, a little change was observed after four months. The products (jam) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…The TSS of jelly increased non-significantly and this increase in TSS during storage might be due to conversion of polysaccharides into monosaccharide and soluble disaccharides (Gould, 1983). Our trend of results are in conformity with the findings of Kumar et al (2007) in guava leather, Ahmed et al (2011) in spota jam, Kuchi et al (2014) in guava jelly bar and Sindumathi and Amutha (2014) in coconut based jam. Gel firmness of jelly is dependent on per cent pectin along acidity of jelly.…”
Section: Resultssupporting
confidence: 91%
“…The TSS of jelly increased non-significantly and this increase in TSS during storage might be due to conversion of polysaccharides into monosaccharide and soluble disaccharides (Gould, 1983). Our trend of results are in conformity with the findings of Kumar et al (2007) in guava leather, Ahmed et al (2011) in spota jam, Kuchi et al (2014) in guava jelly bar and Sindumathi and Amutha (2014) in coconut based jam. Gel firmness of jelly is dependent on per cent pectin along acidity of jelly.…”
Section: Resultssupporting
confidence: 91%
“…This deviation may be due to processing, varietals difference, agro climatic conditions, maturity level etc. (Kulkarni et al 2007;Gopalan et al 2000;Pawar et al 2011;Ganjayal et al 2005;Ahmed et al 2011;Mahattanatawee et al 2006;Ma et al 2004;Jain and Jain 1998;Ilamaran and Amutha 2007;Rodriguez et al 2011;Almeida et al 2011). Figure 1 shows the relation between shear stress and shear rate of enzyme clarified sapota juice of 55.6 o brix at different temperatures and Fig.…”
Section: Physicochemical Characteristicsmentioning
confidence: 99%
“…Stability in TSS content is reported in wood apple jam (Vidhya and Narain, 2011). Ahmed et al (2011) reported that the TSS of sapota jam remained as 67 °brix from initial to four months of storage period. As in the present study, Ehsan et al (2003) also reported a negligible increase in TSS of watermelon jam from 68.6 to 68.9  brix.…”
Section: Microbial Count Of Tender Coconut Blended Jam During Storagementioning
confidence: 97%